Osteoarchaeology and the History of Medicine in our experience - Iorio, Silvia; Badino, Paola; Gorini, Ilaria; Aliverti, Massimo (Acta Biomedica Atenei Parmensis, 2019)
The encounter between archaeology and medicine is no longer the result of sporadic or intermittent research. Stemming from different areas of expertise and training, as well as historical sciences, archaeology, biology and medicine, common investigative objectives must come together in a coordinated manner. However, defining the boundaries of different areas of work, collaboration, interferences and interconnections is not an easy task.